Sex and Care: The Evolutionary Psychological Explanations for Sex Differences in Formal Care Occupations - Tay, Peter Kay Chai; Ting, Yi Yuan; Tan, Kok Yang (Frontiers in Psychology, 2019)
Men and women exhibit clear differences in occupational choices. The present article elucidates sex differences in terms of formal care occupational choices and care styles based on evolutionary psychological perspectives. Broadly, (1) the motivation to attain social status drives male preference for occupations that signals prestige and the desire to form interpersonal affiliation underlies female preference for occupations that involve psychosocial care for people in need; (2) ancestral sex roles leading to sexually differentiated cognitive and behavioral phenotypic profiles underlie present day sex differences in care styles where men are things-oriented, focusing on disease management while women are people-oriented, focusing on psychosocial management. The implications for healthcare and social care are discussed and recommendations for future studies are presented.